The Cavo-suprahepaticophlebography in Posterosuperior Hydatic Cyst of Liver - Davidenko, Nicolás; Tiscornia, Eduardo; Silva García, Ernesto; Davidenko, Antonio (Cirugía del Uruguay, 1980)
Report on a series of 25 patients with hydatic cyst detected in the superior segments of liver through diverse radiological procedures ( oleohepatography, cavography and suprahepaticography) and confirmated by operation.